Whole genome analysis of echinocandin non-susceptible Candida Glabrata clinical isolates: a multi-center study in China - Yi Li; Xin Hou; Ruoyu Li; Kang Liao; Ling Ma; Xiaoming Wang; Ping Ji; Haishen Kong; Yun Xia; Hui Ding; Wei Kang; Ge Zhang; et al. (BMC Microbiology, 2023)
Abstract Background Candida glabrata is an important cause of invasive candidiasis. Echinocandins are the first-line treatment of invasive candidiasis caused by C. glabrata. The epidemiological echinocandin sensitivity requires long-term surveillance and the understanding about whole genome characteristics of echinocandin non-susceptible isolates was limited. Results The present study investigated the echinocandin susceptibility of 1650 C. glabrata clinical isolates in China from August 2014 to July 2019. The in vitro activity of micafungin was significantly better than those of caspofungin and anidulafungin (P < 0.001), assessed by MIC50/90 values. Whole genome sequencing was conducted on non-susceptible isolates and geography-matched susceptible isolates. Thirteen isolates (0.79%) were resistant to at least one echinocandin. Six isolates (0.36%) were solely intermediate to caspofungin. Common evolutionary analysis of echinocandin-resistant and echinocandin-intermediate isolates revealed genes related with reduced caspofungin sensitivity, including previously identified sphinganine hydroxylase encoding gene SUR2. Genome-wide association study identified SNPs at subtelometric regions that were associated with echinocandin non-susceptibility. In-host evolution of echinocandin resistance of serial isolates revealed an enrichment for non-synonymous mutations in adhesins genes and loss of subtelometric regions containing adhesin genes. Conclusions The echinocandins are highly active against C. glabrata in China with a resistant rate of 0.79%. Echinocandin non-susceptible isolates carried common evolved genes which are related with reduced caspofungin sensitivity. In-host evolution of C. glabrata accompanied intensive changing of adhesins profile.